TNF-α preactivation of neutrophils in women with lipids metabolism disturbances using hormonal replacement therapy - Stetkiewicz, Tomasz; Stachowiak, Grzegorz; Surkont, Grzegorz; Romanowicz-Makowska, Hanna; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2005)
Lipids peroxidation, especially LDL cholesterol is well known effect of reactive oxygen intermediates (ROI) activity in organism. Lipids peroxidation products have ahterogenic activity, increasing ischaemic heart disease risk Aim of study: Comparison of hormonal replacement therapy on priming of neutrophils by TNF-α, measured in peripheral blood using the method of chemiluminescency in groups of women with lipids metabolism disturbances and normal lipids values. Material and methods: Study group consists of 29 women with hipercholesterolaemia (mean age 54.3÷5.0) and 29 women with hiperlipidaemia (hipercholesterolaemia or hipertriglyceridaemia (mean age 54.6÷4.8). Control group includes 27 women with normal lipids concentrations (mean age 53.8÷5.2). Oxydative burst of neutrophils was evaluated in 20a l peripheral blood sample before, after 3 and 6 months of this therapy. Oxydative burst was observed after neutrophils acivation with stimulators: fMLP, PMA and zymosan with or without previous preactivation with 10 ng. TNF-α. Chemiluminescency associated with oxydation burst was measured with Luminometr 1251, BioOrbit, Turku, Finland in stable temperature during 30 minutes (15 readings). Results: Evaluating HRT influence on neutrophils priming by TNF-α in mentioned groups in case of some chemiluminescence parameters, interactions between HRT duration and priming were observed. During HRT decrease of neutrophils priming was faster in groups with hipercholesterolaemia and hipertriglyceridaemia than in women with normal lipids concentrations. This interactions do not allow to conclude general relations. Conclusion: Priming of neutrophils by TNF-α does not depend on lipids metabolism disturbances.